If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + v) + -48v = 8 Remove parenthesis around (8 + v) 8 + v + -48v = 8 Combine like terms: v + -48v = -47v 8 + -47v = 8 Add '-8' to each side of the equation. 8 + -8 + -47v = 8 + -8 Combine like terms: 8 + -8 = 0 0 + -47v = 8 + -8 -47v = 8 + -8 Combine like terms: 8 + -8 = 0 -47v = 0 Solving -47v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Divide each side by '-47'. v = 0 Simplifying v = 0
| 12x+45x=-6 | | 3.6(2x-7.5)=4.2(2-2.5x) | | 2x+1.5=3.9 | | 5=x+3-8 | | -88=(-8)y | | 8m=-16+40 | | 41-11=5(x-3) | | 10=x-x-5 | | 2(2y+3)+2=4y+5 | | 1650=8x+2t^2 | | 2(5-2x)=15+6x | | 6x+4=4(3x+2) | | -100x^2+25x-1=0 | | 8m=6+2m | | (x-6)(5x^2+x-8)= | | 3y+3=312 | | 5y+25=-5-y | | -2x+5=x-12 | | 15-2=15 | | (x^3+4x^2-5x)-(4x^3+x^2-7)= | | -x(-8)-4y=16 | | -4x+9=35 | | 13k+3(k+11)=8k+-7 | | 3y+2=12-y | | 6b-.2=7b | | 5d-27=108 | | 25(C-55)=23750 | | X(2x+1)+4(2x+1)=0 | | 2*(3t^2)*(4t^2-1)=x | | 19+x=14 | | 2k+-2.6=12 | | -6t-8=-7t |